The impact of sports on the normal functioning of the prostate gland: A review - Anton V. Ershov (ZAO "Consilium Medicum", 2023)
This article explores the relationship of physical activity to the normal functioning of the prostate gland. The biomechanism of hormonal activity during exercise was studied, and special attention was paid to the biomechanism of an actively working muscle and the release of myokines. The analysis of the relationship between myokines and the functioning of the prostate gland was carried out. It has been established that physical activity reduces the risk of developing prostate diseases and is an important method of prevention.